A Manganese-Based Coordination Polymer; Synthesis, Structure and Catalytic Activity. (July 2016) - Alghool, Samir; Slebodnick, Carla; Khaled, Khaled F.
Atwo-dimensional manganese(II)-based coordination polymer [Mn(L)4 (CH3 COO)2 ] [L=1, 4-bis(1-imidazolyl)benzene] has been synthesised. Its X-ray structure revealed that the layers of the 2D structure are stacked together by two types of weak interactions extending to form a three-dimensional supramolecular structure. The thermal stability of this coordination polymer is described and the compound has been used as a heterogeneous catalyst in oxidation of cyclohexene to cyclohexene oxide. A density functional study of structural parameters, position of the HOMO and LUMO energies, electrophilicity and global hardness is reported.